2021
DOI: 10.3390/molecules26237088
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the Metal–Nitrile Bonding in an Organo-Diiron System

Abstract: Nitriles (N≡CR) are ubiquitous in coordination chemistry, yet literature studies on metal–nitrile bonding based on a multi-technique approach are rare. We selected an easily-available di-organoiron framework, containing both π-acceptor (CO, aminocarbyne) and donor (Cp = η5−C5H5) ligands, as a suitable system to provide a comprehensive description of the iron–nitrile bond. Thus, the new nitrile (2–12)CF3SO3 and the related imine/amine complexes (8–9)CF3SO3 were synthesized in 58–83% yields from the respective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 88 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…In fact, previous findings indicated that R may significantly affect the chemistry of this class of complexes [ 37 ]. Compounds [1a–d]CF 3 SO 3 were converted into the respective acetonitrile adducts [ 40 ] using the trimethylamine- N -oxide (TMNO) strategy, which is often reliable with cationic complexes based on the {M 2 Cp 2 (CO) 3 } core with M = Fe or Ru [ 41 , 42 , 43 , 44 ]. The resulting derivatives [1a NCMe –1d NCMe ]CF 3 SO 3 were used in all cases as freshly prepared reactants.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, previous findings indicated that R may significantly affect the chemistry of this class of complexes [ 37 ]. Compounds [1a–d]CF 3 SO 3 were converted into the respective acetonitrile adducts [ 40 ] using the trimethylamine- N -oxide (TMNO) strategy, which is often reliable with cationic complexes based on the {M 2 Cp 2 (CO) 3 } core with M = Fe or Ru [ 41 , 42 , 43 , 44 ]. The resulting derivatives [1a NCMe –1d NCMe ]CF 3 SO 3 were used in all cases as freshly prepared reactants.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative PPh 3 /MeCN replacement was achieved by heating a solution of 1 in acetonitrile at reflux, affording complex 2 in 95% yield ( Scheme 1 ). Note that nitrile ligands usually behave as labile ones and are easily replaced by phosphines when coordinated to group 8 41 44 or other transition metals. 45 , 46 In the present case, the reversed reaction is probably favored by steric factors arising from two bulky triphenylphosphines occupying adjacent coordination sites in 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The common feature in the synthesis of 2 – 4 is the elimination of one carbon monoxide ligand by means of the trimethylamine‐N‐oxide strategy. [ 48 ] Thus, when the reaction with trimethylamine‐N‐oxide is conducted in acetonitrile, a labile nitrile adduct is formed, [ 49 ] and the subsequent treatment with either NaBH 4 , NBu 4 CN or LiCl results in the formation of neutral products. Within the 2a – c series, [Fe 2 (μ‐H)Cp 2 (CO) 2 {μ‐CN (Me)(Xyl)}], 2c , was previously reported, [ 50 ] whereas [Fe 2 (μ‐H)Cp 2 (CO) 2 {μ‐CN (Me)(R)}] (R = 4‐C 6 H 4 OMe, 2a ; R = Cy, 2b ) are described here for the first time.…”
Section: Resultsmentioning
confidence: 99%